Combined treatment with memantine/es‐citalopram for older depressed patients with cognitive impairment: a pilot study. (11th November 2015) - Pelton, Gregory H.; Harper, Oliver L.; Roose, Steven P.; Marder, Karen; D'Antonio, Kristina; Devanand, D. P.
Abstract : Objective: The objective of the study is to assess combined antidepressant and memantine treatment in older patients presenting with depression and cognitive impairment. Methods: Thirty‐five depressed patients with cognitive impairment participated in this open‐label pilot study. We evaluated whether, over a 48‐week period, combined antidepressant (primarily es‐citalopram) and memantine treatment was effective in the treatment of cognitive impairment and depression. Neuropsychological testing was performed, and antidepressant response monitored at baseline and at the 12, 24, and 48‐week time points. Results: Treatment with escitalopram (mean daily dose 18.62 mg, SD 5.15) and memantine (mean daily dose 13.62 mg, SD 6.67) was associated with improvement in Hamilton Depression Rating Scale scores over the 48‐week study period. Patients demonstrated significant improvement in the primary outcome of cognitive performance (Selective Reminding Test total immediate recall; SRT‐IR) over the 48‐week treatment period ( p = 0.0147). Significant improvement was also observed in measures of naming and verbal fluency but not in the other cognitive domains. One of the 35 patients (2.9%) converted to Alzheimer's disease over the 48‐week treatment period. In the amnestic mild cognitive impairment subsample ( n = 22), the conversion rate was 4.5%, a rate lower than in other reports of patients with DEP‐CI. Conclusions: In this open‐label trial, combined antidepressant and memantine treatment in patients with DEP‐CI was associated with improved cognition and a low rate of conversion to dementia compared with published studies in patients with DEP‐CI. Although limited by the open‐label study design that incorporates practice effects that can improve cognitive test performance, the findings suggest the need for a larger randomized placebo‐controlled trial. Copyright © 2015 John Wiley & Sons, Ltd.